HCnH- anion chains with n ≤ 8 are nonlinear and their permanent dipole makes them potential candidates for astronomical observation - Bâldea, Ioan (Molecules, 2022)
To be detectable in space via radio astronomy, molecules should have a permanent dipole moment. This is the plausible reason why HCnH chains are underproportionally represented in the interstellar medium in comparison with the isoelectronically equivalent HCnN chain family, which is the most numerous homologous series astronomically observed so far. In this communication, we present results of quantum chemical calculations for the HCnH family at several levels of theory: density functional theory (DFT/B3LYP), coupled-cluster expansions (ROCCSD(T)), and G4 composite model. Contradicting previous studies, we report here that linear HCnH− anion chains with sizes of astrochemical interest are unstable (i.e., not all calculated frequencies are real). Nonlinear cis and trans HCnH− anion chains turn out to be stable both against molecular vibrations (i.e., all vibrational frequencies are real) and against electron detachment (i.e., positive electroaffinity). The fact that the cis anion conformers possess permanent dipole is the main encouraging message that this study is aiming at conveying to the astrochemical community, as this makes them observable by means of radio astronomy.
Published: 12 May 2022
Das "-" ist bei HCnH- hochgestellt, das "n" bei HCnH- ist tiefgestellt
Gesehen am 30.06.2022